A new moss salamander, genus Nototriton (Caudata: Plethodontidae), from the Cordillera de Talamanca, in the Costa Rica-Panama border region - Arias, Erick; Kubicki, Brian (Zootaxa, 2018)
A new salamander belonging to the genus Nototriton, subgenus Nototriton, is described from the Caribbean slopes of the southeastern Cordillera de Talamanca in Costa Rica, within Parque Internacional La Amistad, at an elevation ca. 1500 m a.s.l. This new taxon is distinguished from its congeners by its morphological characteristics and by its differentiation in DNA sequences of the 16S rRNA, cytochrome oxidase subunit I (COI), and cytochrome b mitochondrial genes. This new species represents the southernmost extension known for the genus Nototriton.